Evaluation of an extended‐release formulation of ceftiofur crystalline‐free acid in koi (Cyprinus carpio). Issue 6 (16th April 2015) - Grosset, C.; Weber, E. S.; Gehring, R.; Sanchez‐Migallon Guzman, D.; Campbell, L. A.; Enz, C.; Groff, J. M.; Tell, L. A.
<x xml:space="preserve">Abstract</x> The use of an extended release ceftiofur crystalline‐free acid formulation (CCFA, Excede For Swine®, Pfizer Animal Health) in koi was evaluated after administration of single intramuscular (i.m.) or intracoelomic (i.c.) doses. Twenty koi were divided randomly into a control group and four treatment groups (20 mg/kg i.m., 60 mg/kg i.m., 30 mg/kg i.c., and 60 mg/kg i.c.). Serum ceftiofur‐free acid equivalents (CFAE) concentrations were quantified. The pharmacokinetic data were analyzed using a nonlinear mixed‐effects approach. Following a CCFA injection of 60 mg/kg i.m., time durations that serum CFAE concentrations were above the target concentration of 4 μg/mL ranged from 0.4 to 2.5 weeks in 3 of 4 fish, while serum CFAE concentrations remained below 4 μg/mL for lower doses evaluated. Substantial inter‐individual variations and intra‐individual fluctuations of CFAE concentrations were observed for all treatment groups. Histological findings following euthanasia included aseptic granulomatous reactions, but no systemic adverse effects were detected. Given the unpredictable time vs. CFAE concentration profiles for treated koi, the authors would not recommend this product for therapeutic use in koi at this time. Further research would be necessary to correlate serum and tissue concentrations and to better establish MIC data for Aeromonas spp. isolated from naturally infected koi.